Navigating biosafety regulatory frameworks for genetic engineering in Africa: a focus on genome editing and gene drive technologies - Rabuma, Tilahun; Moronta-Barrios, Felix; Craig, Wendy (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Genome editing and gene drive technologies are increasingly gaining attraction in Africa, with researchers exploring their potential applications in agriculture, health and the environment.Acknowledging that robust regulatory frameworks are crucial in facilitating the development and utilization of these technologies, informed decision-making is, however, being impeded by the fragmented information availability and readiness of regulatory authorities on the continent.Objectives: This study investigates the regulatory frameworks governing genome editing and gene drive technologies in African countries, identifies common regulatory challenges and proposes actionable solutions.Methods: Primary data were collected through questionnaires and complemented by analysing existing biosafety regulations from online databases and scientific literature.Results: Our findings suggest that while a few African countries have recently updated their regulatory frameworks, many are still under discussion. Challenges to development and implementation include limited resources, expertise, awareness, and public resistance.These findings underscore the urgent need for further development in regulatory capacities.By shedding light on these challenges, our study could provide African regulators with valuable insights to guide the formulation of effective regulatory frameworks. Such frameworks are essential for harnessing the potential of genome editing and gene drive technologies while safeguarding human health and the environment in Africa.